Remote and proximal sensing applications for soil conservation and management - Bellinaso, Henrique (2022)
This doctoral thesis aimed to develop techniques for remote and proximal sensing and digital soil mapping applied to soil management and conservation. Chapter 1 provides a general introduction to the work. In Chapter 2, the objective was to evaluate the use of different sensor systems in predicting the content of one of the most important attributes of the soil than clay, to support management practices in a small agricultural property. For this, data from the FieldSpec laboratory and airborne AISA-FÉNIX hyperspectral sensors, and from the orbital optical sensors of LANDSAT 8-OLI, Sentinel 2-MSI and PlanetScope were used. In the third chapter a similar approach was adopted, however, a larger (regional) study area was adopted to map soil erodibility, an important parameter used in modeling the prediction of soil loss by water erosion. For this, a multi-temporal image of exposed soil called SYSI was obtained. In the fourth chapter, a collection of Landsat images (1985 to 2019) was used to understand the spatio-temporal dynamics of exposure of (discovered) soils cultivated with sugarcane covering the Piracicaba region. In the second chapter, the results found showed better prediction performance for the laboratory and on-board sensors, followed by the Landsat 08-OLI and Sentinel 2-MSI sensors. The PlanetScope sensor presented the lowest prediction performance (R2 0.26 and 0.14). In the third chapter, the techniques used allowed the creation of digital maps of soil erodibility more suitable for use in small areas than erodibility maps generated from currently available legacy soil maps. In the fourth chapter, it was possible to identify the positive impact of the end of the sugarcane burning, in the reduction of the area of unprotected soil during the year. However, it was found that sandy soils are more often unprotected due to their lower productive potential. This higher frequency of exposure can potentiate the loss of organic carbon from the soil, since it is associated with conventional practices of soil tillage for a new planting of the sugarcane crop. More clayey soils have a lower frequency of exposure due to their greater productive potential, which leads to a lower need for sugarcane renewal. Finally, chapter 5 makes general considerations and conclusions about the work as a whole.